LITERASI AI SEBAGAI KOMPETENSI ABAD KE-21: ANALISIS KONSEPTUAL DAN IMPLIKASI PENDIDIKAN - Bambang Suripto (Jurnal Ekonomi Dan Bisnis, 2026)
The rapid advancement of artificial intelligence (AI) technology requires individuals to be prepared to understand, use, and critically evaluate its impacts. AI literacy has become a strategic key in fostering a society that is adaptive to digital transformation. However, conceptual understanding and the implementation of AI literacy remain diverse and uneven, particularly in developing countries. This study aims to systematically review the literature addressing the definitions, dimensions, learning approaches, as well as the challenges and implications of AI literacy development. The method employed is a systematic review of 20 scholarly articles published between 2018 and 2024, sourced from reputable databases such as Scopus and Google Scholar. The findings indicate that AI literacy encompasses cognitive, affective, and sociocultural dimensions, along with increasingly relevant technical and ethical aspects. The lack of explicit curricula, teacher training, and policy integration constitutes major barriers. This study emphasizes the importance of synergy among governments, educational institutions, and industry sectors in enhancing AI literacy capacity in a contextual and inclusive manner. The theoretical and practical implications of this review provide a foundation for the development of policies, curricula, and assessment instruments that support AI-based education.